A survey of Free-Living Amoebae (FLAs) in Nasal Mucosa of Healthy Individuals using Culture-based Method - Arab-Mazar, Zahra; Niyyati, Maryam; Behniafar, Hamed; Lasjerdi, Zohreh (Novelty in Biomedicine, 2021)
Free-living amoebas (FLAs) are facultative parasites, and some of them can be highly pathogenic for animals and humans. These protozoan are found in abundance in environmental resources such as freshwater and soil, and thus the possible colonization of such FLA is probable. Our previous studies showed that Acanthamoeba spp. can colonize nasal mucosa of immunosuppressed patients. However, there was no report of colonization of free-living amoebae in healthy individuals in Iran. The present study was conducted to investigate the possibility that FLAs are the normal flora of the nasal mucosa. Overall, 46 nasal swab samples were collected from healthy individuals and cultured on a 1.5% non-nutrient agar (NNA) plate enriched with a lawn of heat-killed Escherichia coli. The plates were incubated at room temperature. After one week, the plates were microscopically examined, and this was continued for one month. None of the samples were found positive for FLAs. Our findings may indicate that FLAs are not the normal flora of the nasal mucosa, or their number is so limited in the nasal mucosa that they cannot be isolated by the method used. However, supplementary and comprehensive studies are recommended.